2020
DOI: 10.1371/journal.pcbi.1007929
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating between negative cooperativity and ligand binding to independent sites using pre-equilibrium properties of binding curves

Abstract: Negative cooperativity is a phenomenon in which the binding of a first ligand or substrate molecule decreases the rate of subsequent binding. This definition is not exclusive to ligand-receptor binding, it holds whenever two or more molecules undergo two successive binding events. Negative cooperativity turns the binding curve more graded and cannot be distinguished from two independent and different binding events based on equilibrium measurements only. The need of kinetic data for this purpose was already re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Interestingly, a recent saturation transfer difference NMR study reported an unusually low Hill coefficient of 0.69 for aspartate binding to liposome-reconstituted Glt Ph ( Hall et al, 2020 ). A Hill coefficient below one may reflect negative cooperativity or result from multiple binding states with distinct affinities ( Cattoni et al, 2015 ; Sevlever et al, 2020 ; Wang and Pan, 1996 ). Distinguishing these possibilities requires a kinetic approach ( Cattoni et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent saturation transfer difference NMR study reported an unusually low Hill coefficient of 0.69 for aspartate binding to liposome-reconstituted Glt Ph ( Hall et al, 2020 ). A Hill coefficient below one may reflect negative cooperativity or result from multiple binding states with distinct affinities ( Cattoni et al, 2015 ; Sevlever et al, 2020 ; Wang and Pan, 1996 ). Distinguishing these possibilities requires a kinetic approach ( Cattoni et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent saturation transfer difference NMR study reported an unusually low Hill coefficient of 0.69 for aspartate binding to liposome-reconstituted GltPh (Hall et al, 2020). A Hill coefficient below 1 may reflect negative cooperativity or result from multiple binding states with distinct affinities (Cattoni, Chara, Kaufman, & Gonzalez Flecha, 2015;Sevlever, Di Bella, & Ventura, 2020; Z. X. Wang & Pan, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although low-molecular-weight ligands do not take part in the processes of protein folding [ 32 , 33 , 34 ] and DNA melting, the latter are substantially cooperative. Thus, cooperativity significantly affects both intracellular and intercellular regulation of life processes [ 25 , 35 , 36 , 37 , 38 ].…”
Section: Statistical Entropy In Description Of Living Systems At the ...mentioning
confidence: 99%
“…There is also a known problem that the results of calculating the curves in a model with included anticooperative interactions between ligands coincide with the results of calculations in the presence of heterogeneous binding, but not cooperative. To solve this problem, the researcher needs to set up binding kinetics experiments [ 38 ].…”
Section: Model Of Adsorption and Entropy Evaluationmentioning
confidence: 99%